Preparation method and application of injectable bone repair hydrogel with antioxidant function
By preparing an injectable bone repair hydrogel with antioxidant function, combining Cu/Zn HA powder with other biologically active substances, the poor biocompatibility and mismatch of mechanical strength of existing bone tissue engineering materials in vivo are solved. The problem of this problem has achieved better bone repair results and clinical application prospects.
Patent Information
- Application Number
- CN202411721578.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
Existing bone tissue engineering materials have poor biocompatibility in the body, which is difficult to firmly connect with bone tissue, and the mechanical strength does not match, which can easily lead to recurrence of fractures.
Prepare an injectable bone repair hydrogel with antioxidant function, and form Cu/Zn by reacting calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, sodium dodecyl sulfate and diammonium hydrogen phosphate. HA powder, combined with phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, epigallocatecin gallate and methacrylylated gelatin, was prepared by light crosslinking.
The hydrogel has better proliferative, osteoinductive and mechanical strength, can more effectively impart osteogenic activity to osteoblasts, improve the local microenvironment, and has excellent antibacterial ability, which is suitable for subchondral bone repair.
Smart Images

Figure CN119455094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a preparation method and application of an injectable bone repair hydrogel with antioxidant function. Background Art
[0002] With the development of social economy and the explosive growth of vehicles, bone defects caused by trauma, infection, tumors and congenital diseases have led to a rapid increase in people's demand for bone repair. In recent years, the use of tissue engineering technology to construct in vitro or transplant biologically functional tissue-engineered bones in vivo has brought new hope to patients with bone defects and is currently recognized as an ideal method for bone defect repair. Although bone tissue engineering has gradually formed a relatively complete construction theory and technical route, it still has defects such as insufficient biological activity and limited tissue regeneration capacity in the body, making the types and quantities of bone tissue engineering products that can be used clinically so far extremely limited. Therefore, improving the performance of tissue-engineered bones is of great scientific and economic significance for the development of advanced tissue-engineered bone products for clinical use.
[0003] At present, the commonly used methods for the treatment of bone defects in clinical practice are: (1) Conservative treatment: including bed rest, drug analgesia, brace external fixation, etc. However, conservative treatment cannot correct large bone defects and requires long-term bed rest, which is prone to cause other related complications. (2) Bone transplantation: Autologous bone transplantation is the gold standard for bone defect repair and is still the most commonly used and most effective bone repair method in clinical practice. However, its large-scale application is limited by its source and secondary trauma. In addition, the use of allogeneic bone also has the risk of immune rejection and pathogen infection. (3) Biomedical material bone repair technology: It has been widely used in clinical bone defect repair. The first generation is "inert biomaterials", such as stainless steel and alloys. This generation of materials is currently used in clinical applications such as fixed bone screws and artificial bone joints. The second generation is "bioactive, degradable materials", such as calcium phosphate bone cement (CPC) and polylactic acid. After this generation of materials is placed in the bone defect site, the newly grown bone tissue can fuse with the material and the interface can penetrate each other.
[0004] However, inert biomaterials used as filling materials and fixed prostheses have poor biocompatibility and are difficult to connect firmly with bone tissue, making them prone to loosening and sinking in the body. At the same time, although the surgery restores the patient's defective structure, the mechanical strength of the material does not match that of human bones, resulting in recurrent fractures at the surgical defect.
[0005] The biomedical materials currently used in clinical practice have the following problems: (1) they can only repair bone defects but cannot promote rapid regeneration of cells near the defect to achieve bone repair; (2) the material itself has poor biocompatibility and has certain cytotoxicity, which inhibits the proliferation of surrounding osteoblasts; (3) in terms of mechanical strength, its compressive strength and elastic modulus are both high, making it brittle and not tough, which does not match the properties of human bones, which have high compressive strength and low elastic modulus, and is prone to recurrence of fractures at the surgical defect. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a preparation method and application of an injectable bone repair hydrogel with antioxidant function. The injectable bone repair hydrogel has better proliferation promotion, osteoinductivity and mechanical strength, is an ideal material suitable for subchondral bone repair, and has good clinical application prospects.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing an injectable bone repair hydrogel with antioxidant function is provided, comprising the following steps:
[0008] (1) reacting calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, sodium dodecyl sulfate solution and diammonium hydrogen phosphate solution to form a suspension, adjusting the pH value at room temperature, reacting at room temperature, discarding the supernatant, washing the precipitate, and freeze-drying to obtain Cu / ZnHA powder;
[0009] (2) dissolving lithium phenyl-2,4,6-trimethylbenzoylphosphinate in phosphate buffered saline and stirring to obtain an initiator solution;
[0010] (3) adding the Cu / Zn HA powder obtained in step (1) to the initiator solution obtained in step (2), stirring for reaction, and then ultrasonicating to obtain a mixed solution;
[0011] (4) adding epigallocatechin gallate powder to the mixed solution obtained in step (3) and stirring to dissolve, then adding methacryloyl gelatin and continuously stirring, injecting into a mold, and cross-linking under light to obtain an injectable bone repair hydrogel.
[0012] Furthermore, in step (1), the molar concentrations of calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, and sodium dodecyl sulfate solution are 0.81 M, 0.02 M, 0.02 M, and 0.03 M, respectively, and the (Ca+Zn+Cu) / P molar ratio is 1.55.
[0013] Furthermore, in step (1), aqueous ammonia is added at room temperature to adjust the pH value to 8, and the mixture is reacted at room temperature for 4 hours and aged for 24 hours.
[0014] Furthermore, in step (2), stirring is performed at 30-50° C. for 10-20 min.
[0015] Furthermore, in step (3), stirring is performed at 30-50° C. for 24 h and ultrasonication is performed for 30 min.
[0016] Furthermore, in step (4), methacryloyl gelatin is added and stirred at 30-50° C. for 2 h, and cross-linked under 405 nm light conditions for 20 s.
[0017] Furthermore, in the injectable bone repair hydrogel, the mass percentages of Cu / Zn HA powder, epigallocatechin gallate powder, initiator solution and methacryloyl gelatin are 0.5%, 0.1%, 0.25% and 10%, respectively.
[0018] The present invention also provides an injectable bone repair hydrogel prepared by the preparation method of the injectable bone repair hydrogel with antioxidant function.
[0019] The present invention also provides application of the injectable bone repair hydrogel in bone defect repair.
[0020] The present invention has the following beneficial effects:
[0021] 1. Compared with the traditional preparation of HA powder modified by antibacterial metal ions, the present invention uses epigallocatechin gallate (EGCG) to modify the powder. On the one hand, EGCG can form a complex with metal ions to achieve the sustained release of metal ions in the system, and EGCG has an antibacterial effect and can cooperate with antibacterial metal ions in antibacterial effect. On the other hand, EGCG has an antioxidant function and can effectively remove excess ROS in and outside the body. In addition, EGCG can interact with GelMA through hydrogen bonding to enhance the mechanical strength of the hydrogel. At the same time, the effective combination of HA nanoparticles and hydrogel is enhanced. Based on this, the present invention successfully prepared an injectable hydrogel with antibacterial, antioxidant and bone repair-promoting functions.
[0022] 2. During the preparation, EGCG powder and Cu / Zn HA powder were added. 2+ 、Zn 2+ The metal polyphenol nanoformulation was synthesized by the coordination interaction between the two, and the injectable bone repair hydrogel was obtained, which reduced the Cu 2+ 、Zn 2+ The coordination between copper and zinc ions and EGCG can retain the biological effects of EGCG while also enabling Cu 2+ 、Zn 2+ Slow release, this cross-linking strategy enables Cu 2+ 、Zn 2+The release time window of the concentration is greatly improved. Compared with traditional hydrogels, the GE-Cu / ZnHA injectable bone repair hydrogel obtained by the present invention has better proliferation promotion, bone induction and mechanical strength, can better endow osteoblasts with osteogenic activity, improve the local microenvironment, and has excellent antibacterial ability. It is an ideal material suitable for subchondral bone repair and has good clinical application prospects.
[0023] 3. The injectable bone repair hydrogel of the present invention has the characteristics of simple preparation, injectability, and arbitrary shaping. Compared with ordinary degradable materials, GE-Cu / Zn HA injectable bone repair hydrogel also has the advantages of giving osteoblasts osteogenic activity, improving the local microenvironment, and having excellent antibacterial ability. The purpose of adding Cu / Zn HA powder is that Cu / Zn can promote osteoblast repair and angiogenesis at the bone defect site, and Cu has significant antibacterial ability. The purpose of adding EGCG powder is that EGCG has the effect of scavenging oxygen free radicals, thereby improving the local microenvironment at the bone defect site. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the crosslinkability of the hydrogels obtained in Example 1 and Comparative Examples 1-3;
[0025] Figure 2 The scanning electron microscope and EDS images of the hydrogels obtained in Example 1 and Comparative Examples 1-3 are shown;
[0026] Figure 3 Schematic diagram of bacterial proliferation of the hydrogel obtained in Example 1 and Comparative Examples 1-3 co-cultured with Staphylococcus aureus;
[0027] Figure 4 Live-dead staining images of the hydrogels obtained in Example 1 and Comparative Examples 1-3 after co-culture with Staphylococcus aureus;
[0028] Figure 5 The scanning electron microscope images of the hydrogels obtained in Example 1 and Comparative Examples 1-3 after co-culture with Staphylococcus aureus;
[0029] Figure 6 The live-dead staining and cell proliferation test diagrams of the hydrogels obtained in Example 1 and Comparative Examples 1-3 after co-culture with osteoblast precursor cells;
[0030] Figure 7 A schematic diagram of ALP staining and content after co-culturing the hydrogels obtained in Example 1 and Comparative Examples 1-3 with osteoblast precursor cells;
[0031] Figure 8 Schematic diagram of Alizarin red staining and content after co-culturing the hydrogels obtained in Example 1 and Comparative Examples 1-3 with osteoblast precursor cells;
[0032] Fig. 9 Schematic diagram of the results of osteoblast-related gene expression experiments after co-culturing the hydrogels obtained in Example 1 and Comparative Examples 1-3 with osteoblast precursor cells. DETAILED DESCRIPTION
[0033] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0034] Example 1
[0035] A method for preparing an injectable bone repair hydrogel with antioxidant function comprises the following steps:
[0036] (1) Calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, sodium dodecyl sulfate solution and diammonium hydrogen phosphate solution are reacted to form a suspension, ammonia water is added at room temperature to adjust the pH value to 8, the suspension is reacted for 4 hours and aged for 24 hours at room temperature, the supernatant is discarded, the precipitate is washed, and the suspension is freeze-dried to obtain Cu / Zn HA powder; the molar concentrations of calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, and sodium dodecyl sulfate solution are 0.81M, 0.02M, 0.02M, and 0.03M, respectively, and the (Ca+Zn+Cu) / P molar ratio is 1.55;
[0037] (2) dissolving lithium phenyl-2,4,6-trimethylbenzoylphosphinate in phosphate buffered saline and stirring at 40° C. for 15 minutes to obtain an initiator solution;
[0038] (3) adding the Cu / Zn HA powder obtained in step (1) to the initiator solution obtained in step (2), stirring at 40° C. for 24 h, and ultrasonicating for 30 min to obtain a mixed solution;
[0039] (4) Add epigallocatechin gallate powder to the mixed solution obtained in step (3), stir and dissolve for 30 minutes, then add methacrylated gelatin and continue stirring at 40° C. for 2 hours, inject into a mold, and crosslink for 20 seconds under 405 nm light conditions to obtain an injectable bone repair hydrogel (denoted as GE-Cu / Zn HA).
[0040] Among them, in the injectable bone repair hydrogel, the mass percentages of Cu / Zn HA powder, epigallocatechin gallate powder, initiator solution and methacryloyl gelatin are 0.5%, 0.1%, 0.25% and 10% respectively.
[0041] Comparative Example 1
[0042] GelMA (methacryloyl gelatin) was mixed with deionized water to prepare a hydrogel commonly used in clinical practice, which was denoted as G.
[0043] Comparative Example 2
[0044] EGCG was added to GelMA (methacryloyl gelatin), mixed evenly, and then mixed with LAP and cross-linked to prepare EGCG-containing GelMA hydrogel, which was denoted as GE.
[0045] Comparative Example 3
[0046] Calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, sodium dodecyl sulfate solution and diammonium hydrogen phosphate solution are reacted to form a suspension, wherein the (Ca+Zn+Cu) / P molar ratio is 1.55, and ammonia water is added to adjust the pH of the reaction environment to 8. After reacting at room temperature for 4 hours, the suspension is aged for 24 hours, the supernatant is poured out, the precipitate is washed, and the Cu / Zn HA powder is obtained after freeze-drying. The obtained Cu / Zn HA powder is added to liquid GelMA, mixed evenly, and then mixed with LAP and cross-linked to prepare a GelMA hydrogel containing Cu / Zn HA powder, which is recorded as G-Cu / Zn HA.
[0047] The crosslinkability of the hydrogels obtained in Example 1 and Comparative Examples 1-3 is as follows: Figure 1 shown.
[0048] Depend on Figure 1 It can be seen that the hydrogel obtained in Example 1 is cross-linkable.
[0049] Experimental Example 1
[0050] The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to physical characterization experiments. The process was as follows: the hydrogels were polished into discs with a diameter of 10 mm and a thickness of 2 mm, and then freeze-dried and observed under a scanning electron microscope and EDS photographed. The results are shown in FIG. Figure 2 shown.
[0051] Depend on Figure 2 It can be seen that the surfaces of the two groups of hydrogels, G-Cu / Zn HA and GE-Cu / Zn HA, are covered with Cu / Zn HA powder, which increases the surface area of the material and improves the roughness of the hydrogel surface, which is more conducive to cell adhesion.
[0052] Experimental Example 2
[0053] 1. The antibacterial properties of the hydrogels obtained in Example 1 and Comparative Examples 1-3 were tested. The bacteria were Gram-positive bacteria Staphylococcus aureus (S. aureus). The sterilized and prepared sheet hydrogels with a diameter of 5 mm and a thickness of 2 mm in each group were placed on a curing ring, and the hydrogels were suspended in a bacterial culture medium in a 24-well plate and mixed with a bacterial suspension (10 5-10 7 CFU / mL) for 4 hours, then dilute to a certain concentration and apply to the plate, place it in a 37°C constant temperature incubator and invert it for overnight incubation, count the number of colonies and calculate the inhibition rate. Figure 3 shown.
[0054] Depend on Figure 3 It can be seen that when EGCG or Cu / Zn HA was added to GelMA, the number of bacteria decreased, and the 4h antibacterial rates of GE and G-Cu / Zn HA scaffolds were 58% and 87%, respectively. For the GE-Cu / Zn HA scaffold, the antibacterial rate was as high as 95%.
[0055] 2. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to a bacterial live-death experiment. The process was as follows: the sterilized and prepared sheet-shaped hydrogels with a diameter of 5 mm and a thickness of 2 mm in each group were placed on a curing ring, and the hydrogels were suspended in a bacterial culture medium in a 24-well plate and mixed with a bacterial suspension (10 5 -10 7 CFU / mL) overnight, and the bacteria were stained. Figure 4 shown.
[0056] Depend on Figure 4 It can be seen that no obvious red fluorescence was observed under the field of view of the G scaffold, indicating that SAU was in a viable state. However, after the addition of EGCG or Cu / Zn HA, the integrity of the bacterial biofilm was lost to varying degrees, and a large number of bacterial deaths occurred under the field of view, indicating that both EGCG and Cu / Zn HA could inhibit the growth of bacteria.
[0057] 3. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to bacterial SEM experiments. The process was as follows: each group of sheet-shaped hydrogels with a concave center diameter of 5 mm and a thickness of 2 mm were prepared. After sterilization, the bacterial suspension (10 5 -10 7 CFU / mL) and then 100 μL was dropped into the depression of the hydrogel, transferred to a 37°C constant temperature incubator for incubation for 12 h, and then fixed with 2.5% glutaraldehyde solution (Glutaric dialdehyde, China) at 4°C for 24 h, dehydrated in 60%, 70%, 80%, 90%, and 100% ethanol solutions, and dried at room temperature to observe the bacterial structure on the surface of the hydrogel. The results are shown in Figure 5 shown.
[0058] Depend on Figure 5It can be seen that the bacteria in the G scaffold grew in large quantities and completely covered the hydrogel surface, showing a typical spherical shape with a smooth and intact membrane, indicating that there was no adverse effect on bacterial survival. In contrast, the bacterial morphology in GE, G-Cu / Zn HA, and GE-Cu / Zn HA changed, and at the same time, the bacterial density decreased and the bacterial proliferation was inhibited.
[0059] Experimental Example 3
[0060] 1. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to live and dead cell staining experiments. The process was as follows: MC3T3-e1 (osteoblast precursor cells) were inoculated in a 24-well plate and divided into four groups (corresponding to G, GE, G-Cu / Zn HA, and GE-Cu / Zn HA, respectively). Four parallel wells were set in each group, and each well had about 1×10 4 Cells were added to each group, and the extracts of the hydrogels obtained in Comparative Examples 1-3 and Example 1 were added to each group. The proliferation of cells was detected by CCK-8 method after culturing for 1, 4 and 7 days. That is, after removing the culture medium, 180 μL of fresh culture medium and 20 μL of CCK-8 cell proliferation detection solution were added to each well. After incubation for 1 hour, the absorbance value was detected at a wavelength of 450 nm using an ELISA instrument; and after culturing for 3 and 5 days, the live and dead cell staining reagent was used for staining. The results are shown in the figure. Figure 6 shown.
[0061] Depend on Figure 6 It can be seen that a large number of live cells stained with Calcein-AM green were seen on the surface of each group, while only a few dead cells stained with red were seen. The number of live cells was GE-Cu / Zn HA>G-Cu / Zn HA>GE>G, while there was no significant difference in the number of dead cells, indicating that each group had good biocompatibility. At the same time, G-Cu / Zn HA and GE-Cu / Zn HA also showed good proliferative activity.
[0062] At the same time, the cell proliferation rate of the G group hydrogel was slow, while the proliferation rates of GE and G-Cu / Zn HA were increased after adding EGCG and Cu / ZnHA powders, respectively, indicating that EGCG and Cu / Zn HA powders have pro-proliferation activity. The cell proliferation rate of the GE-Cu / ZnHA group hydrogel was the highest on the 4th and 7th days, proving that under the combination of EGCG and Cu / Zn HA powders, the GE-Cu / Zn HA group hydrogel has the strongest effect in promoting the proliferation of MC3T3 cells.
[0063] 2. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to ALP staining and content experiments. The process was as follows: MC3T3-e1 (osteoblast precursor cells) were inoculated in a 24-well plate and divided into four groups (corresponding to G, GE, G-Cu / Zn HA, and GE-Cu / ZnHA, respectively). Four parallel wells were set in each group, and each well had about 1×10 4 After 3 days of inoculation, the α-MEM medium was replaced with osteogenic differentiation medium (supplemented with 10 mM β-glycerophosphate, 10 nM dexamethasone and 50 μM vitamin C), and fresh medium was replaced every 2 days. After 7 and 14 days of culture, the ALP content in each group of wells was measured using an alkaline phosphatase detection kit, and the ALP of each group of materials was stained using a BCIP / NBT alkaline phosphatase colorimetric kit. The results are shown in Figure 2. Figure 7 shown.
[0064] Depend on Figure 7 It can be seen that compared with the G group, the staining of the GE group was not significantly enhanced at 7 days, and the content was not statistically significant. The ALP content increased at 14 days, indicating that EGCG has a certain role in regulating osteogenesis. The ALP staining of the G-Cu / Zn HA and GE-Cu / Zn HA hydrogels was significantly enhanced at 7 and 14 days, and the ALP content increased significantly, indicating that the Cn released from the Cu / Zn HA powder 2+ and Zn 2+ The bone mineralization effect on MC3T3-e1 is stronger than that on EGCG.
[0065] 3. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to Alizarin Red staining and content test experiments. The process was as follows: MC3T3-e1 (osteoblast precursor cells) were inoculated in a 24-well plate and divided into four groups (corresponding to G, GE, G-Cu / Zn HA, GE-Cu / Zn HA, respectively). Each group was set with 4 parallel wells, and each well had about 1×10 4 After 3 days of inoculation, the α-MEM medium was replaced with osteogenic differentiation medium (supplemented with 10 mM β-glycerophosphate, 10 nM dexamethasone and 50 μM vitamin C), and fresh medium was replaced every 2 days. After 21 days of culture, the calcium nodules were stained with Alizarin Red S staining solution for 5-10 minutes. After staining, 500 μL of 10% hexadecylpyridinium chloride was added to each culture well to dissolve the calcium nodules. After the calcium nodules were completely dissolved, the absorbance value at a wavelength of 562 nm was measured with an enzyme reader. The results are shown in the figure. Figure 8 shown.
[0066] Depend on Figure 8It can be seen that with the passage of time, the size and density of calcium nodules were obvious on the 21st day. However, the changes observed in the G group were not as significant as those in the other groups. This indicates that EGCG and Cu / Zn HA powder can promote osteogenesis in vitro. There are still statistical differences between GE and G-Cu / Zn HA, indicating that the osteogenesis effect of Cu / Zn HA powder is stronger than that of EGCG, which is due to the effect of Zn 2+ The ability of Cu to induce bone formation and mineralization around implants 2+ Can enhance Zn 2+ In the combination of EGCG and Cu / Zn HA powder, GE-Cu / Zn HA produced the most calcium nodules.
[0067] 4. The hydrogels obtained in Example 1 and Comparative Examples 1-3 were subjected to an osteogenesis-related gene expression experiment. The process was as follows: MC3T3-e1 (osteoblast precursor cells) were inoculated in a 6-well plate and divided into four groups (corresponding to G, GE, G-Cu / Zn HA, and GE-Cu / Zn HA, respectively). Three parallel wells were set in each group, and each well had about 1×10 5 After 3 days of inoculation, the α-MEM medium was replaced with osteogenic differentiation medium (supplemented with 10 mM β-glycerophosphate, 10 nM dexamethasone and 50 μM vitamin C), and fresh medium was replaced every 2 days. After 14 days of culture, the expression of ALP (alkaline phosphatase), OCN (osteocalcin), OPN (osteopontin), and Runx-2 (Runt-related transcription factor 2) in cells was detected by fluorescence quantitative PCR. The results are shown in Fig. 9 shown.
[0068] Depend on Fig. 9 It can be seen that the expression levels of the above-mentioned osteogenesis-related genes on the surface of GE-Cu / Zn HA were upregulated compared with those of G, GE, and G-Cu / ZnHA (P<0.05); the expression levels of OCN on the surfaces of G-Cu / Zn HA and GE-Cu / Zn HA were similar (P>0.05), and higher than those of G and GE (P<0.05). The expression levels of ALP, OPN, and Runx2 on the surface of GE-Cu / Zn HA were higher than those of G, GE, and G-Cu / Zn HA (P<0.05); it can be seen that GE-Cu / Zn HA had the most obvious upregulation of the expression levels of osteogenesis-related genes in MC3T3-e1.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an injectable bone repair hydrogel with antioxidant function, characterized in that: The following steps are involved: (1) reacting calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, sodium dodecyl sulfate solution and diammonium hydrogen phosphate solution to form a suspension, adjusting the pH value at room temperature, reacting at room temperature, discarding the supernatant, washing the precipitate, and freeze-drying to obtain Cu / Zn HA powder; (2) dissolving lithium phenyl-2,4,6-trimethylbenzoylphosphinate in phosphate buffered saline and stirring to obtain an initiator solution; (3) adding the Cu / Zn HA powder obtained in step (1) to the initiator solution obtained in step (2), stirring for reaction, and then ultrasonicating to obtain a mixed solution; (4) adding epigallocatechin gallate powder to the mixed solution obtained in step (3) and stirring to dissolve, then adding methacryloyl gelatin and continuously stirring, injecting into a mold, and cross-linking under light to obtain an injectable bone repair hydrogel.
2. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In step (1), the molar concentrations of calcium nitrate tetrahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate and sodium dodecyl sulfate solution are 0.81M, 0.02M, 0.02M and 0.03M respectively, and the (Ca+Zn+Cu) / P molar ratio is 1.
55.
3. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In step (1), aqueous ammonia is added at room temperature to adjust the pH value to 8, and the mixture is reacted at room temperature for 4 hours and aged for 24 hours.
4. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In step (2), stirring is performed at 30-50° C. for 10-20 min.
5. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In step (3), the mixture is stirred at 30-50° C. for 24 h and ultrasonicated for 30 min.
6. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In step (4), methacryloyl gelatin is added and stirred at 30-50° C. for 2 h, and cross-linked under 405 nm light for 20 s.
7. The method for preparing the injectable bone repair hydrogel with antioxidant function as claimed in claim 1, characterized in that: In the injectable bone repair hydrogel, the mass percentages of Cu / Zn HA powder, epigallocatechin gallate powder, initiator solution and methacryloyl gelatin are 0.5%, 0.1%, 0.25% and 10% respectively.
8. The injectable bone repair hydrogel prepared by the method for preparing the injectable bone repair hydrogel with antioxidant function according to any one of claims 1 to 7.
9. Use of the injectable bone repair hydrogel according to claim 8 in repairing bone defects.